A Novel Proportional-Derivative Sliding Mode for Load Frequency Control - Jianping Guo (IEEE Access, 2024)
This paper presents a novel sliding mode control method in controlling load frequency in an interconnected power system, which utilizes the proportional-derivative sliding mode surface. In addition, the stability of the proposed method is verified mathematically. In order to prove the effectiveness of the proposed scheme, the simulation is made under different cases. Both frequency error and area control error (ACE) are converged to zero, so the control aim is arrived. Under parameters change, the control aim can still be achieved, which confirms the robustness of the proposed scenario. In addition, the overshoot is lower, the response time is quicker, and the chattering effect is more decreased with the proposed approach comparing to the traditional sliding mode control and PID control scheme, which illustrate the superiority of the proposed method. Finally, the simulation of the proposed control scheme is compared with full order sliding mode control, which is an advanced sliding mode control method. From the waveform of the simulation, the steady error is smaller, the response time is quicker for the proposed control method, so the superiority of the proposed method is also validated.